2014
DOI: 10.1371/journal.pcbi.1003640
|View full text |Cite
|
Sign up to set email alerts
|

A Normative Theory of Forgetting: Lessons from the Fruit Fly

Abstract: Recent experiments revealed that the fruit fly Drosophila melanogaster has a dedicated mechanism for forgetting: blocking the G-protein Rac leads to slower and activating Rac to faster forgetting. This active form of forgetting lacks a satisfactory functional explanation. We investigated optimal decision making for an agent adapting to a stochastic environment where a stimulus may switch between being indicative of reward or punishment. Like Drosophila, an optimal agent shows forgetting with a rate that is lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The ability to forget confers adaptive advantages to animals living in a changing environment (68,69); for example, memory inconsistent with the current circumstance needs to be quickly removed or suppressed, which otherwise may endanger one's survival. We here used a simple reversal learning paradigm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to forget confers adaptive advantages to animals living in a changing environment (68,69); for example, memory inconsistent with the current circumstance needs to be quickly removed or suppressed, which otherwise may endanger one's survival. We here used a simple reversal learning paradigm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The clearance of irrelevant memories would open new storage space and facilitate retrieval, making the brain more efficient for error-free retrieval (Rosenzweig et al, 2002). Moreover, it seems intuitive that some level of active forgetting would offer increased fitness by reducing recurring and unwanted situations or unrewarded perseveration (Kraemer and Golding, 1997; Storm, 2011; Brea et al, 2014). One strain of Drosophila named rovers explore their environment actively whereas an allelic variant, named sitters, are much more stationary.…”
Section: The Viewpoint Of Active Biological Forgetting Of Memory Tracesmentioning
confidence: 99%
“…Why we forget, has been an intriguing and central question in psychology and neuroscience for more than a century. Even though forgetting is often thought of as a failure or limitation of the brain, recent studies support the view that forgetting is a biologically regulated function of the brain allowing optimal adaptability to an ever-changing environment (Berry and Davis, 2014; Berry et al, 2012; Shuai et al, 2010; Brea et al, 2014). In the fruit fly Drosophila , we recently showed that the very same set of dopamine neurons (DANs) that signal through one receptor to form aversive olfactory memories, also signal through a separate receptor after learning to forget these memories (Berry et al, 2012).…”
Section: Introductionmentioning
confidence: 99%